High School Students’ Perspectives towards the Mathematics Teaching Profession - Dhakal, Prem Kumari; Dhungana, Hem Lal (Journal of Mathematics Education, 2026)
This study aims to identify high school students’ perspectives towards mathematics teaching profession. The study applied a quantitative survey questionnaire as the instrument of data collection. One private and one public secondary schools of Surkhet district of Nepal were selected as the sample schools based on the number of students enrolled in Science and Mathematics background after completion of School Education Examination. The students of grade twelve, who were studying Mathematics in Science stream, were the participants of this study. The questionnaire was distributed individually to 80 participants with the help of their mathematics teachers after describing the objective of the study. Collected data was analyzed descriptively using percentage, pie charts, and bar graphs. The data indicated that most preferred profession of the students was medical sector. The second preferred profession was IT. Around 25% students were interested on IT. The study revealed that most of the students were not interested in teaching mathematics as their future profession.